DESIGN OF INFORMATION SYSTEM FOR PAYMENT OF WORKERS' WAGES AND PREPARATION OF FINANCIAL REPORTS ON GARMENT UD KELAMBI ANYAR - Puspitasari, Ni Made; Sulastra, I Made Dwi Jendra; Putrayasa, I Made Agus (Jurnal Ilmiah Manajemen, Ekonomi, & Akuntansi (MEA), 2024)
Information technology developments are beneficial to businesses worldwide, particularly in Indonesia. Businesses that use information technology effectively can store and manage data, expedite business operations, and manage data. Information systems used in accounting are one area where technology is crucial. The purpose of this project is to develop and construct an information system application for the UD Kelambi Anyar clothing firm that will be used for financial report preparation and worker salary payment. For worker salaries, this company historically used manual records, which presented a number of challenges including the possibility of errors, information delays, and difficulty in finding data. This application was developed using the Software Development Life Cycle (SDLC) approach using the Waterfall paradigm. Planning, analyzing, designing, implementing, testing, and implementing are the stages of system development. Microsoft Access 2019 was used to create the database for this application, while Visual Basic Applications (VBA) was used to write the code. An information system application that facilitates the recording of worker service payments and the preparation of financial reports, such as profit and loss statements and balance sheets, is the outcome of this research project for UD Kelambi Anyar. In addition to a filter menu to make data searching for employee salary reports easier, this program has a username and password feature to ensure user security. It is envisaged that using this application will improve the financial transaction process' accuracy and efficiency and speed up the process of making management choices.